Kültepe hüyüğünde çıkan üç tablet / Three Tablets from the City Mound of Kültepe - Bilgiç, Emin (1966)
Anatolia = Anadolu; to be continued in Anatolia 9 (kt. g/t 36; g/t 42; H/T 330; from the palace of Waršama).